Three coordination polymers built by quaternary‐ammonium‐modified isophthalic acid. Issue 5 (22nd April 2021) - Wang, Li-Fei; Liu, Xing-Gui; Meng, Mei-Mei; Xu, Yong-Kai; Zhu, Rui; Zhang, Rui; Lu, Zhen-Zhong; Huang, Wei
Abstract : Three metal–organic frameworks constructed by quaternary‐ammonium‐modified isophthalic acid are reported. Abstract : Three coordination polymers based on quaternary‐ammonium‐modified isophthalic acid, namely, catena ‐poly[[[aqua‐μ2 ‐bromido‐di‐μ3 ‐hydroxido‐methanoldinitratotetracopper(II)]‐bis{μ4 ‐5‐[2‐(tripropylazaniumyl)ethoxy]benzene‐1, 3‐dicarboxylato}] nitrate], {[Cu4 Br(C19 H28 NO5 )2 (NO3 )2 (OH)2 (CH4 O)(H2 O)]NO3 } n, 1, poly[μ3 ‐bromido‐μ2 ‐bromido‐bromido‐μ3 ‐hydroxido‐{μ4 ‐5‐[2‐(tripropylazaniumyl)ethoxy]benzene‐1, 3‐dicarboxylato}tricopper(II)], [Cu3 Br3 (C19 H28 NO5 )(OH)] n, 2, and poly[bromido{μ3 ‐5‐[2‐(tripropylazaniumyl)ethoxy]benzene‐1, 3‐dicarboxylato}zinc(II)], [ZnBr(C19 H28 NO5 )] n, 3, were obtained by solvothermal reactions. Coordination polymer (CP) 1 contains tetranuclear Cu4 units, in which the four Cu atoms are linked by two μ3 ‐OH − groups into a Cu4 (OH)2 cluster, which are in turn linked by 5‐[2‐(tripropylazaniumyl)ethoxy]benzene‐1, 3‐dicarboxylate (cpa − ) ligands into a chain structure. CP 2 also contains a tetranuclear Cu4 (OH)2 cluster and these are linked with CuBr3 units into chains. The chains are then connected by cpa − ligands into a two‐dimensional layered structure. CP 3 contains a two‐dimensional layer structure built by binuclear Zn2 units and cpa − ligands. The Br − counter‐anions of the quaternary ammonium groups all take part in the construction of the polymeric networks.